Pengaruh Formulasi Pakan Hijauan (Rumput Gajah, Kaliandra dan Gamal) terhadap Pertumbuhan dan Bobot Karkas Domba - Firdus Firdus (Jurnal Agripet, 2010)
The effect of forage formulation (elephant grass, kaliandra, and gamal leaves) on the growth and carcass of sheep